MUSCLE STRENGTH EVALUATION AFTER ANTERIOR CRUCIATE LIGAMENT RECONSTRUCTION USING ISOKINETIC DYNAMOMETRY - Maria Ganeva; Miglena Tsvetkova-Gaberska; Iliya Kanelov; Nevena Pencheva (Peytchinski Publishing, 2023)
Purpose: The aim of this report is to measure and analyse the isometric and isokinetic (concentric) peak torque (PT) of knee extensors and flexors of the involved and uninvolved limb of twin professional football players over one year post anterior cruciate ligament reconstruction (ACLR). To calculate the unilateral and bilateral asymmetry indexes and compare the athlete's PT values with sport-specific and position-specific data. Case description: Strength measurements of the knee extensors and flexors were conducted on two ACLR football players (twins) on the involved and uninvolved limbs in isometric and concentric modes of muscle contractions, and unilateral/bilateral asymmetry indexes were calculated. Results: The peak torque isometric data indicated that the strength characteristics of the involved leg extensors in both patients were significantly lower compared to the uninvolved limb and were indicators of higher secondary injury risk. The first athlete's concentric peak torque values showed relatively good return-to-sport results, while the second football player returned to sport having not met the recovery criteria. Both athletes require additional specific muscle strength exercises on the extension and flexion muscle groups to reach the ACL reconstruction recovery targets. Conclusions: In this case report, the possibilities of isokinetic dynamometric testing in an isometric and concentric mode of football players to more accurately assess the extent of the muscle strength deficiency and asymmetry are demonstrated. This more precise information allows to the creation of correct training and therapeutic program to recover the knee muscle groups' strength and unilateral/bilateral strength balance to avoid reinjury.